Electrometric measurement of plasma, erythrocyte, and whole blood cholinesterase activities in healthy human volunteers - Mohammad, F. K. (Springer-Verlag, 2007)
INTRODUCTION: The measurement of blood cholinesterase activity is a useful tool for monitoring exposure to organophosphate and carbamate insecticides. Blood cholinesterase activity is measured colorimetrically or electrometrically. Recently, a simple and practical electrometric method has been described and validated for measuring blood cholinesterase activity in people and animals. The purpose of the present report was to use the modified electrometric technique for measuring blood (plasma, erythrocyte and whole blood) cholinesterase activities in apparently healthy human volunteers in Mosul, Iraq. METHOD: Cholinesterase activities in the plasma, erythrocytes, and whole blood of healthy male (n = 72) and female (n = 31) volunteers were measured by an electrometric method; the method involved the addition of 0.2 ml of blood sample to 3 ml of distilled water followed by 3 ml of barbital-phosphate buffer solution (pH 8.1). The pH (pH1) of the mixture was measured, and then 0.1 ml of 7.5% of acetylcholine iodide, as a substrate, was added. The reaction mixture was incubated at 37°C for 20 minutes. The pH (pH2) of the reaction mixture was measured after the end of the incubation period. Enzyme activity was expressed as ΔpH/20 min = pH1 − pH2 − (ΔpH of the blank). The blank was without the blood sample. Following in vitro inhibition of pseudo cholinesterase by quinidine sulfate, true cholinesterase activity was estimated in the plasma of the subjects. After in vitro addition of the organophosphate (chlorpyrifos and methidathion, 0.5 and 1 μM) and carbamate (carbaryl, 5 and 10 μM) insecticides to the reaction mixtures, inhibitions of blood cholinesterases were measured. RESULTS: Mean reference cholinesterase activities (ΔpH/20 min) in the plasma, erythrocytes, and whole blood of male subjects were 0.98, 1.39, and 1.41, respectively. Females were 0.85, 1.22, and 1.23, respectively. Ten minutes after in vitro addition of quinidine sulfate to inhibit pseudo cholinesterase activity in the plasma, the estimated true cholinesterase activities in males and females were 0.08 and 0.07 ΔpH/20 min, respectively. The percentage of true cholinesterase in the plasma of males and females was 8.2. Using the modified electrometric method, various percentages of cholinesterase inhibitions in the plasma, erythrocytes, and whole blood were detected after in vitro addition of the organophosphate insecticides (chlorpyrifos and methidathion) and the carbamate insecticide (carbaryl) to the reaction mixtures. CONCLUSIONS: These findings are the first collective report of human plasma, erythrocyte, and whole blood cholinesterase activities as determined by the modified electrometric method, and they could serve as reference points for future studies that involve human exposure to anticholinesterase pesticides.